Multisatellite observations of an intensified equatorial ionization anomaly in relation to the northern Sumatra earthquake of March 2005. Issue 6 (2nd June 2014) - Ryu, K.; Lee, E.; Chae, J. S.; Parrot, M.; Oyama, K.‐I.
Abstract Here we report multisatellite observations of ionospheric disturbances in relation to the occurrence of the M8.7 northern Sumatra earthquake of 28 March 2005. The DEMETER (Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions) and CHAMP (Challenging Minisatellite Payload) satellite data were investigated to find possible precursory and postevent phenomena. It was found that EIA (equatorial ionization anomaly) strength expressed in the apex height, derived from the CHAMP plasma density profile, was intensified along the orbits whose longitudes were close to the epicenter within about a week before and after occurrence of the earthquake. Increases in electron and O+ density along the orbits close to the epicenter were also observed in the DEMETER measurements. The normalized equatorial plasma density derived from the DEMETER measurements showed intensification about a week before and after the earthquake reaching maximum the day after the shock and afterward disappearing. In addition, similar behavior of the EIA enhancements related to the M8.0 Pisco earthquake of 15 August 2007 was observed. Surveys of space weather and geomagnetic activities excluded the possibility that these fluctuations were caused by changes in space weather or by a geomagnetic storm. Statistical analyses of the longitudinal variation revealed that the EIA was enhanced in the west of the epicenter and reduced in the east of the epicenter, and this fits the "increased conductivity" model. Based on these observations, we proposed a revised view of seismo‐ionospheric coupling in the region of the geomagnetic equator, to explain the EIA features observed in this study.